The Rationale of Public Policies to Cope the Daunting Challenging of Food Security: A Case Study of Punjab (Pakistan) (Journal of Asian Development Studies, 2026)
Food security is a menace and sinister to socio-economic development however it has close connection to public policies in order to transform a mild state of nausea into pander the food requirements of the people. A great deal of existing studies focuses on partially analyzing food security dimension with respect to particularly food availability and connections to household food security. Public policies have unceasing enticement on food security that has been remained limited priority of the policy makers. This study has examined the impacts of closely related public policies especially on all dimension of food security in a Pakistan’s selected area. Primary data has collected from 140 respondents of the six union councils of the area in Punjab Pakistan. In Logit Regression, results illustrate that public policies regarding water irrigation, improved seed and fertilizers policy, price support and health policies have significant and positive impacts on the food security of the targeted area while climate change has significantly been adverse impact particularly on food availability of the area from 2015 to 2017. Food inflation colligation with inflation have negative impacts on food security that shows people’s purchasing power has been impaired in one hand while average yield has been decreased due to configuration of input and output prices distortion. There summarized the results which shows government interventions concentrate more on food availability while other dimensions of food security are neglected in priority benchmark in the implementation and regulative authorities. Findings of this study propose that public policies need coordination and priority-based realization both from the government administrations and public sides.